Applicability of clinical simulation scenario in the teaching of laryngeal mask insertion (Research, Society and Development, 2022)
Objective: To evaluate the applicability of the clinical simulation scenario with nursing students in teaching laryngeal mask insertion through the simulation design scale. Method: Cross-sectional study with a quantitative approach, developed with nursing students from a public higher education institution. Results: Predominance of females, single (93%). The analysis referring to the five dimensions of the simulation design scale showed grade 5 (5.8), considering the assessment I totally agree, followed by grade 4 (5.3), I agree with the statement. In this way, students consider that the objectives and information provided were sufficient and the information adequate and directed to promote their understanding process for decision making. During the debriefing, the feedback and reflection right after the service were considered by the students as an opportunity to analyze their own behavior in the actions performed, and finally, the realism within the proposed scenario resembles a real situation. Conclusion: it emphasizes the importance of testing previously planned scenarios and that simulation is an active methodology that improves decision-making and contributes to the student's critical thinking.